Corporate Investment and Political Stability: Role of an Enormous Anti-Corruption Campaign, Ownership Structure, and Financial Constraints in An Emerging Economy - Manh Huu Nguyen; Giang Thi Huong Vuong; Trung Duc Nguyen (SAGE Open)
This paper examines the impact of political stability on Vietnamese corporate investment over the period 2010 to 2020. The findings indicate a positive relationship between political stability and corporate investment. This association persists when employing alternative measures of corporate investment and political stability and after addressing endogeneity concerns. Notably, this work identifies a considerable positive effect of political stability on corporate investment following Vietnam’s extensive anti-corruption campaign. Further analysis reveals that this positive impact is particularly significant for firms experiencing higher financial constraints and those with considerable institutional and foreign ownership. Most interestingly, the effect of political stability on corporate investment is consistent across both state-owned and non-state-owned firms. Our paper contributes to the corporate finance literature by pioneering an investigation into how political stability influences corporate investment in a developing Southeast Asian economy. Furthermore, it provides an empirical foundation for understanding speculative motives and real-option theory within the finance domain. The paper’s findings have practical implications for business executives and policymakers in developing nations facing serious political instability driven by corruption issues. JEL Classification: E60, G30, G11.